1991
DOI: 10.1210/jcem-72-3-607
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile Insulin Delivery has Greater Metabolic Effects than Continuous Hormone Administration in Man: Importance of Pulse Frequency

Abstract: The aim of this study was to see if the greater effect of insulin on hepatic glucose output when insulin is given using 13-min pulses in man remains when the same amount of insulin is delivered using 26-min pulses. The study was performed on nine male healthy volunteers submitted to a 325 min glucose-controlled glucose iv infusion using the Biostator. The endogenous secretion of pancreatic hormones was inhibited by somatostatin. Three experiments were performed in each subject on different days and in random o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
58
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 20 publications
1
58
0
Order By: Relevance
“…The improved insulin action could be attributed to insulininsulin receptor kinetics, where insulin binding causes internalization of the insulin receptor for a brief period, allowing it to resurface before the next insulin secretory burst arises. This could explain why the impact of pulsatile delivery is frequency-dependent [16].…”
Section: Impact Of Pulsatile Insulin Secretion On Insulin Actionmentioning
confidence: 99%
“…The improved insulin action could be attributed to insulininsulin receptor kinetics, where insulin binding causes internalization of the insulin receptor for a brief period, allowing it to resurface before the next insulin secretory burst arises. This could explain why the impact of pulsatile delivery is frequency-dependent [16].…”
Section: Impact Of Pulsatile Insulin Secretion On Insulin Actionmentioning
confidence: 99%
“…Insulin is secreted in discrete secretory bursts occurring approximately every 4 min (9,10). Some studies have suggested that the pulsatile pattern of insulin delivery to the liver is important in insulin action (11,12). Regulation of insulin secretion is predominantly accomplished by modulation of burst mass, which is increased in response to glucose ingestion or infusion, sulfonylurea ingestion, and GLP-1 infusion (13)(14)(15) and decreased in response to somatostatin or IGF-1 infusion (16) and induction of anesthesia (17).…”
mentioning
confidence: 99%
“…For example, the amplitude of the resulting insulin oscillations in the portal vein is ϳ1,000 pmol/l in the basal state increasing to ϳ4,000 pmol/l after meal ingestion (15). The profile of this insulin concentration wavefront dictates the extent of hepatic insulin clearance in as much as the former is more effective than continuous insulin delivery in suppressing hepatic glucose output (10,16,17). Insulin signaling and insulin extraction by the liver may be optimized by a pulsatile mode of delivery.…”
mentioning
confidence: 99%